Introduction: New Professionalism in Social Work - Bernd Dewe; Hans-Uwe Otto; Stefan Schnurr (Social Work and Society)
Does professionalism have a future in social work or is de-professionalization the leading trend? Throughout the world social welfare and social work are subjects of challenging trends and developments, which are critical to the concept and the opportunities of professionalism in social work. This situation raises theoretical as well as practical and political questions.